PENGARUH GAYA KEPEMIMPINAN MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BANK KALBAR PUSAT PONTIANAK - admin, DESI SURYA PRATIWI B11111046 (Jurnal Manajemen Update, 2016)
This study aims to determine the effect of leadership style, motivation and discipline the performance of employees at PT. Bank Kalbar Pusat Pontianak. PT. Bank Kalbar Pusat Pontianak raise funds engaged in customer deposits, lending and financing, as well as providing other banking services by presenting a diverse range of products and services, both conventional and sharia This type of research is causal research and survey research. Data collection techniques by using primary data and secondary data. The data analysis technique used is the technique of multiple linear regression analysis, processed using SPSS Version 16. Hypothesis testing is done by distributing questionnaires as many as 95 employees of PT. Bank Kalbar Pusat Pontianak Based on the research results it is concluded that the partial leadership style variable, variable work discipline and motivation variables significantly influence the performance of employees at PT. Bank Kalbar Pusat Pontianak Keywords: Style of Leadership, Motivation, Work Discipline and Performance